Ocean feedback on 50–80-day boreal winter intraseasonal oscillation in the Indian Ocean: comparison of atmospheric and coupled CESM2 simulations - Yun Liang; Ruixue Xia; Yan Du (Environmental Research Letters, 2024)
The role of sea surface temperature (SST) variability in the boreal winter intraseasonal oscillation (ISO) over the tropical Indian Ocean (TIO) is investigated in this study using the Community Earth System Model Version 2. An atmospheric general coupled model (AGCM) run forced by daily SSTs derived from a parallel coupled circulation model (CGCM) run is compared with reanalysis and the original coupled simulation. The comparison of atmospheric-coupled GCMs reveals the frequency and spatial tendency of the SST effect on the atmospheric ISO. The 50–80 d component of the ISO over the TIO is significantly intensified in the AGCM run. The SST-to-atmosphere effect is most prominent over the southeastern TIO. In the AGCM run, low-level wind anomalies related to SST appear west of the ISO convection center, contrasting with the previous findings that the SST effect appears east of the convection center.